MODEL DAKWAH MILENIAL UNTUK HOMOSEKSUAL MELALUI TEKNIK KONTINUM KONSELING BERBASIS ALQURAN - Khilman Rofi Azmi (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2019)
The response of da'wa in dealing with the problems of the people in the digital era can be realized through the millennial missionary model. The purpose of the following research is to develop a pilot model of contemporary preaching for homosexuals. The author uses a study of literature studies in developing this model. Nevertheless, a preliminary study was conducted on six research subjects to provide an initial picture in building this model. The technique of giving advice by using Qur’an-based continuum of counseling approach which explained to the six main stages in dealing with homosexual cases, including: 1) identity (self); 2) relationship; 3) feeling distinction (differential of feeling); 4) identification and evaluation (identify and evaluation); 5) spiritual intervention; 6) acceptance of environment. The six continuums are based on nine letters in the Qur'an. In addition, this model also uses a contemporary approach with the use of information channels on various social media platforms in the form of